2017
DOI: 10.1080/10942912.2017.1368549
|View full text |Cite
|
Sign up to set email alerts
|

Rheaological, pasting, and structural properties of potato starch by cross-linking

Abstract: The present study determined the effects of cross-linking with sodium trimetaphosphate (STMP)/sodium tripolyphosphate (STPP) on the structural, rheaological, and pasting properties of potato starch. Starches cross-linked by STMP/STPP at 0.0125%, 0.025%, 0.05%, 0.5%, 5%, and 10% were designated as the cross-linking of potato starch (CLPS)-0.0125, CLPS-0.025, CLPS-0.05, CLPS-0.5, CLPS-5, and CLPS-10, respectively. Scanning electron microscope revealed that STMP/STPP treatment resulted in some changes in the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
1
9
1
1
Order By: Relevance
“…G′ and G″ increased after both thermally induced and HVED enhanced phosphorylations, with a slightly more pronounced effect of the HVED compared to the thermal treatment. This is due to the formation of a strong gel network, according to Heo, Lee and Chang [ 34 ] and may be linked to the larger solubility and water absorption ( Figure 1 ). However, there is no significant difference in G″/G′ values, which are mostly in the range 0.13 – 0.16, with the exception of phosphorylated starches without additional treatment (0.21 for Na 2 HPO 4 and 0.26 for Na 5 P 3 O 10 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…G′ and G″ increased after both thermally induced and HVED enhanced phosphorylations, with a slightly more pronounced effect of the HVED compared to the thermal treatment. This is due to the formation of a strong gel network, according to Heo, Lee and Chang [ 34 ] and may be linked to the larger solubility and water absorption ( Figure 1 ). However, there is no significant difference in G″/G′ values, which are mostly in the range 0.13 – 0.16, with the exception of phosphorylated starches without additional treatment (0.21 for Na 2 HPO 4 and 0.26 for Na 5 P 3 O 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, there is no significant difference in G″/G′ values, which are mostly in the range 0.13 – 0.16, with the exception of phosphorylated starches without additional treatment (0.21 for Na 2 HPO 4 and 0.26 for Na 5 P 3 O 10 ). The values G″/G′ are close to 0.1 showing a formation of a gel network and the elastic nature of formed gels [ 34 ]. Although significant changes in G″/G′ values were not observed in this research, an HVED treatment may induce both decreases of these values due to cross-linking, or increases due to depolymerisation [ 33 ], and Heo, Lee and Chang [ 34 ] reported a decrease in G″/G′ values for a phosphorylated potato starch due to the cross-linking.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S-GNP kompleksinde kümeleşmeye rastlanmamakla birlikte kürelerin boyutunda nişastaya göre bir küçülme gözlenirken, S-GNP-BA kompleksinde ise küçük parçacıklar şeklinde ayrılmalar gösteren bir kümeleşme dikkat çekmektedir. Elde edilen sonuçlar, pürüzsüz, oval ya da yuvarlak şekle sahip doğal patates nişastasının granüllerinin çeşitli derişimlerdeki farklı çapraz bağlayıcılar ile etkileştirildiğinde hafif pürüzlü yüzeyler ve boşluklar sergilediğini gösteren literatürdeki çalışmalar ile uyumludur [42,44,45].…”
Section: Sem Analizi (Sem Analysis)unclassified
“…Present hydrogen bonds in potato starch will be strengthen during cross-linking using cross-linking agent for example acetic anhydride which in turns resulting in starch product that has high resistant towards heat, acid and increase in shearing properties as compared to native and unmodified starch [182]. Another study reported modifying potato starch using sodium trimetaphosphate (STMP) or sodium tripolyphosphate (STPP) as its cross-linking agent resulted in modified starch having desired properties to be applied in food industry such as binding agent, stabilizer and thickener [183].…”
Section: ] Yellow Sorghum Acetylation Benzylation and Hydroxypropmentioning
confidence: 99%